A global and local perspective of interruption frequency in a visual search task - Radović, Tara; Rieger, Tobias; Manzey, Dietrich (Frontiers in Psychology, 2022)
We investigated the impact of frequency of interruptions in a simulated medical visual search task. Participants (N=150) performed the visual search task during which they were interrupted by a number-classification task in 25%, 50%, or 75% of all trials, respectively, reflecting the frequency conditions (i.e., low, mid, high). Target presence (i.e., present vs. absent) and interruption (i.e., uninterrupted vs. interrupted) were varied within-subjects, and interruption frequency was varied between-subjects. Globally, on a frequency condition level, participants in the low frequency condition had longer mean response times (RT) for the primary visual search task than in the high condition, but there were no other performance differences between the three frequency conditions. Locally, on the level of specific interruption effects, accuracy decreased directly after interruptions for target present but not for target absent trials. Furthermore, interruptions caused significant interruption costs, reflected in slower overall RTs in interrupted than in uninterrupted trials. The combined findings show that especially for critical visual search tasks as in the medical field, interruptions—regardless of frequency—should be avoided.